2017
DOI: 10.1021/acs.jpclett.7b00958
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-Mediated Surface Engineering of Silver Nanowires for Surface-Enhanced Raman Scattering

Abstract: We reveal nanoscale morphological changes on the surface of a silver nanowire (AgNW) in the conventional surface-enhanced Raman scattering (SERS) measurement condition. The surface morphology changes are due to the surface plasmon-mediated photochemical etching of silver in the presence of certain Raman probes, resulting in a dramatic increase of Raman scattering intensity. This observation indicates that the measured SERS enhancement does not always originate from the as-designed/fabricated structures themsel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 47 publications
0
32
0
Order By: Relevance
“…The strong Raman band at 1142 cm À1 indicates a chemical conversion from PATP to 4,4 0 -dimercaptoazobenzene (DMAB) upon light irradiation. 11 As discussed, electromagnetic mechanism dominates the observed SERS enhancement. To conrm the role of silicon morphology, we did numerical simulation using the nitedifference time-domain (FDTD) method to investigate the localized electromagnetic eld distributions on AgNPs-coated at and nanoporous silicon surfaces.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…The strong Raman band at 1142 cm À1 indicates a chemical conversion from PATP to 4,4 0 -dimercaptoazobenzene (DMAB) upon light irradiation. 11 As discussed, electromagnetic mechanism dominates the observed SERS enhancement. To conrm the role of silicon morphology, we did numerical simulation using the nitedifference time-domain (FDTD) method to investigate the localized electromagnetic eld distributions on AgNPs-coated at and nanoporous silicon surfaces.…”
mentioning
confidence: 78%
“…[3][4][5][6][7][8][9] Metal materials are mainly employed in fabricating SERS structures, especially gold or silver ones for visible spectrum excitation. 10,11 To date, many nanostructures have been reported that can enhance Raman scattering enormously, leading to so called Raman hot spots, [12][13][14][15] including nanogaps, 16,17 nanostars, 18 nanotriangles and nanorods, 19 mainly due to the introduction of a localized electromagnetic eld under illumination. This kind of enhancement is referred to as the electromagnetic mechanism, which dominates the SERS enhancement in most cases.…”
mentioning
confidence: 99%
“…Nanocrystals, especially semiconductor ones, usually possess unique chemical, electrical, optical and magnetic properties compared to their bulk counterparts . These properties are highly dependent on the chemical composition, size, shape and surface state of the nanocrystals . Therefore, controlled synthesis of nanocrystals is becoming a hot topic in many fields, and lots of efforts have been made to precisely control the morphology and surface state of the nanocrystals .…”
Section: Figurementioning
confidence: 99%
“…[1][2][3] In these fields, it is of great importance to fabricate nanostructures, for both fundamental study and practical applications. [4,5] Nanolithography involves the precise fabrication and interconnection of structures on the nanometer scale, [6] using techniques such as photolithography [7,8] and e-beam lithography [9][10][11] (often combined with etching). These techniques are highly programmable and straightforward and have been used to realize many complexs tructures.…”
mentioning
confidence: 99%
“…[20][21][22][23][24] Silver nanowires (AgNWs) are one of the most studied nanowires due to their promising mechanical, optical and electronic properties. Until now,A gNWsh ave been used as plasmonic waveguides, [25] surface-enhanced Ramans cattering (SERS) platforms, [4] for single-cell endoscopy, [26] as tip-enhanced spectroscopy probes, [27] etc. The polyol synthesized AgNWsp ossess well-definedf ive-fold twin structure and ap entagon-shaped cross section, and their physicochemical properties have been fully characterized by several research groups.…”
mentioning
confidence: 99%